The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1139/t99-133
|View full text |Cite
|
Sign up to set email alerts
|

Shear modulus and damping ratio characteristics of gravelly deposits

Abstract: In this paper, the results of an experimental investigation of dynamic characteristics of gravelly cobble deposits, such as shear modulus (G) and damping ratio (D), are presented. The gravelly cobble deposits are very common in the Taichung metropolitan area of Taiwan where there is an urgent need to determine G and D for dynamic analysis and design of structures. The test program includes measurements of shear wave velocity by the downhole method and large-scale dynamic triaxial tests and resonant-column test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The grain size distribution curves for the in situ and the modified soils are shown in . Consistent test results have been obtained using the same processing method in Lin et al [33]. Proctor compaction tests were conducted through compact modified material into a cylindrical mold in five layers, and each layer was subjected to 25 blows with a 4.5 kg hammer dropped from height of 45.7 cm.…”
Section: Materials and Sample Preparationmentioning
confidence: 60%
“…The grain size distribution curves for the in situ and the modified soils are shown in . Consistent test results have been obtained using the same processing method in Lin et al [33]. Proctor compaction tests were conducted through compact modified material into a cylindrical mold in five layers, and each layer was subjected to 25 blows with a 4.5 kg hammer dropped from height of 45.7 cm.…”
Section: Materials and Sample Preparationmentioning
confidence: 60%
“…Local hanging wall and host to some injections in the Naukluft Thrust 0.28 (Kulhawy, 1975) 2.8 Â 10 10 (Agosta et al, 2007) Chlorite phyllite Local hanging wall and host to some injections in the Naukluft Thrust 0.2 (Nasseri et al, 2003) 5.7 Â 10 9 (Nasseri et al, 2003) Unconsolidated alluvial fan sediments Hanging wall and host to gouge injections in the Badwater Detachment 0.15 (Kulhawy, 1975) 4.4 Â 10 8 (Lin et al, 2000) Dolomitic Breccias (somewhat cohesive) Hanging wall and host to some injections in the Muddy Mountain Thrust 0.3 (Agosta et al, 2007) 2.278 Â 10 10 (Agosta et al, 2007) ( Fig. 7A).…”
Section: Dolostonementioning
confidence: 99%
“…However, only a few tests were performed on gravel and gravelly soils due to the large size of the testing apparatus required. Lin et al [6] pointed out that the large proportion of gravels and the unusual gap grading were the causes for the differing behavior of gravelly deposits. Tanaka [7] found that the G/G 0 -c a relation of an undisturbed soil could be approximately described by that of the reconstituted soil sample.…”
Section: Introductionmentioning
confidence: 99%